The Naik Dango Tradition In The Agricultural Practices Of The Dayak Kanayatn Community, West Kalimantan: A Maqasid Al-Shariah Perspective Of Abd Al-Majid Al-Najjar - Agung Prakoso, Imam; Mukharrom, Tamyiz; Yusdani (LP2M IAIN Palopo, 2025)
This Research examines the Naik Dango tradition practiced by the Dayak Kanayatn community in West Kalimantan from the perspective of Maqasid Syariah Abd al-Majid al-Najjar. This tradition is not only a ritual of gratitude for the harvest, but also a social, ecological, and economic system that supports community food security. The method used is a descriptive qualitative approach with ethnographic techniques through participatory observation, interviews, and documentation. The results of the study indicate that Naik Dango contains values of protection for life (ḥifẓ al-nafs), property (ḥifẓ al-māl), society (ḥifẓ al-mujtama‘), and the environment (ḥifẓ al-muḥīṭ al-māddī), as examined within the framework of maqasid syariah. This tradition supports the preservation of local seeds, solidarity-based food distribution, and intergenerational agrarian education. The conclusion of the study confirms that Naik Dango is a local manifestation of universal Islamic values in maintaining welfare and can be used as an alternative model in formulating sustainable food security strategies based on local wisdom